Ergodic sum rate of transmitting antenna selection in non-orthogonal multiple access for modern systems - Ravi Sankar, M; K. V. Satyanarayana, Dr (International Journal of Engineering and Technology, 2018)
Wireless systems hiring multiple antennas at the transmitter side used for the transmission of the high capacity information through the channels making the system more complex and costlier. To overcome these problems, the multiple antennas at the transmitter side must be reduced and the performance should retained with reduced antennas as earlier. This can be achieved by using the algorithm Transmitting Antenna Selection (TAS) which is carried out by considering the transmission of the information through the channels using the Non-Orthogonal Multiple Access (NOMA). The NOMA algorithm is used to provide the high throughput using the heterogeneous demands in which there is no interference between the transmitted signals from the multiple antennas equipped in a single base station. TAS-NOMA algorithm is proposed in this paper for selecting the best transmitting antenna out of multiple antennas equipped in the base station by using the Ergodic sum rate which is measured at the transmitter side considering the average of the channels capacity.Â Â
Keywords: Tacoma; Ergodic Sum Rate; Channel Capacity; Multiple.